Karakteristik Instrumen Literasi Literasi Matematika SMP pada Konten Aljabar ditinjau dari Perspektif Item Response Theory - Supeno, pujiati_sulihtianing; Indra Meifiani, Nely (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2025)
Mathematical literacy is an essential competency in solving contextual problems, and is the focus of curriculum and assessment development. The quality of mathematical literacy instruments still needs to be studied so that they can accurately reflect students’ abilities. Therefore, this study aims to analyze the characteristics of mathematical literacy instruments of junior high school students on algebraic content using the Item Response Theory (IRT) approach. The instrument was developed based on the AKM (Asesmen Kompetensi Minimum) framework, which includes six questions with a personal and scientific context and a cognitive level of knowledge, application, and reasoning. This study used a quantitative descriptive method with a trial on 231 students from 14 junior high schools in Pacitan Regency. The analysis used the mirt package in the R software, including model compatibility tests, unidimensionality and local independence, parameter estimation, item compatibility, information function, and marginal reliability. The results show that the 1 Parameter Logistics (1PL) model is the best and meets the assumptions of unidimensionality and local independence. The model declared four of the six questions, with the reliability showing a good category of 0,8625. Based on the information function curve, the instrument effectively measures the ability of learners in the range -0,91 to 2,25. These findings show that four question items are declared feasible for measuring mathematical literacy in algebraic content at the junior high school level, which is reviewed from the perspective of IRT analysis. Keywords: 1PL Model, Algebra, IRT, Item Analysis, Mathematical Literacy.